2011
DOI: 10.1038/sj.bjc.6606092
|View full text |Cite
|
Sign up to set email alerts
|

HE4 and CA125 as a diagnostic test in ovarian cancer: prospective validation of the Risk of Ovarian Malignancy Algorithm

Abstract: Background:Recently, a Risk of Ovarian Malignancy Algorithm (ROMA) utilising human epididymis secretory protein 4 (HE4) and CA125 successfully classified patients as presenting a high or low risk for epithelial ovarian cancer (EOC). We validated this algorithm in an independent prospective study.Methods:Women with a pelvic mass, who were scheduled to have surgery, were enrolled in a prospective study. Preoperative serum levels of HE4 and CA125 were measured in 389 patients. The performance of each of the marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

30
232
9
21

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(292 citation statements)
references
References 23 publications
30
232
9
21
Order By: Relevance
“…Our results are somewhat consistent with those of previous studies (Hellström et al, 2003;Moore et al, 2008;Huhtinen et al, 2009;Montagnana et al, 2009;Moore et al, 2009;Moore et al, 2010;Nolen et al, 2010;Bandiera et al, 2011;Molina et al, 2011;Park et al, 2011;Van Gorp et al, 2011;Karlsen et al, 2012;Park et al, 2012), which reported that serum CA125 and HE4 levels were significantly higher in ovarian cancer women than those in benign ovarian tumor women and in healthy women. In accordance with previous observations , our results showed that serum CA125 and HE4 levels were found to be related to FIGO stage with higher concentrations in late stages (stage III/IV) than in early stages (stage I/II).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our results are somewhat consistent with those of previous studies (Hellström et al, 2003;Moore et al, 2008;Huhtinen et al, 2009;Montagnana et al, 2009;Moore et al, 2009;Moore et al, 2010;Nolen et al, 2010;Bandiera et al, 2011;Molina et al, 2011;Park et al, 2011;Van Gorp et al, 2011;Karlsen et al, 2012;Park et al, 2012), which reported that serum CA125 and HE4 levels were significantly higher in ovarian cancer women than those in benign ovarian tumor women and in healthy women. In accordance with previous observations , our results showed that serum CA125 and HE4 levels were found to be related to FIGO stage with higher concentrations in late stages (stage III/IV) than in early stages (stage I/II).…”
Section: Discussionsupporting
confidence: 83%
“…There may be several explanations for the heterogeneity observed among previous studies, and in our opinion, the most intriguing are the differences in the study design, study population, demographic characteristics of patients, ovarian cancer prevalence, sample size, control group (healthy women or women with benign diseases), methods of measuring serum CA125 or HE4 levels (ELISA or chemiluminescent microparticle immunoassay) and cutoff values of CA125/HE4 assays (manufacturer or clinical practice). Furthermore, several studies did not take into account the effect of the uneven distribution of patients in pre-and post-menopausal status, histological subtypes and FIGO stages when interpreting the results of CA125 and HE4 measurements (Moore et al, 2009;Moore et al, 2010;Kim et al, 2011;Montagnana et al, 2011;Ruggeri et al, 2011;Van Gorp et al, 2011). Overall, each of these points theoretically represent a source of heterogeneity among studies likely influencing the markers' diagnostic performances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, women with borderline ovarian tumors have lower serum HE4 concentrations than patients with invasive ovarian cancer. No differences have been identified in serum concentrations of HE4 in patients with various degrees of morphological grade ovarian cancers (van Gorp et al, 2011). Hellström et al demonstrated that the combination of HE4 and CA125 assay provides higher ovarian cancer diagnostic sensitivity and specificity than each biomarker alone (Hellström et al, 2003).…”
mentioning
confidence: 99%